2004
DOI: 10.1103/physrevlett.93.176804
|View full text |Cite
|
Sign up to set email alerts
|

New Class of Level Statistics in Correlated Disordered Chains

Abstract: We study the properties of the level statistics of 1D disordered systems with long-range spatial correlations. We find a threshold value in the degree of correlations below which in the limit of large system size the level statistics follows a Poisson distribution (as expected for 1D uncorrelated-disordered systems), and above which the level statistics is described by a new class of distribution functions. At the threshold, we find that with increasing system size, the standard deviation of the function descr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…It has been observed that the strength of the long-range correlations in such systems can control their electronic properties, as the localization length [3032] or the level statistics [33]. For 1D binary systems, α = 0.5 corresponds to the random binary alloy [34], where the electronic states are exponentially localized.…”
Section: Implications To Correlated-disordered Systemsmentioning
confidence: 99%
“…It has been observed that the strength of the long-range correlations in such systems can control their electronic properties, as the localization length [3032] or the level statistics [33]. For 1D binary systems, α = 0.5 corresponds to the random binary alloy [34], where the electronic states are exponentially localized.…”
Section: Implications To Correlated-disordered Systemsmentioning
confidence: 99%
“…10,18,20,36 The 1 / k ␣ law has also its trace in energy level statistics. 15 All said above unambiguously testifies that studying the properties of disordered systems with long-range-correlated disorder is an attention grabbing task.…”
Section: Introductionmentioning
confidence: 99%
“…8 At the end of the 1980s and beginning of the 1990s it was realized, however, that correlations in disorder may give rise to extended states in low dimensions. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Thus, short-range correlated on-site disorder was found to cause the appearance of extended states at special resonance energies in 1D. They form a set of null measure in the density of states in the thermodynamic limit, [9][10][11][12][13][14] implying the absence of mobility edges in those models.…”
Section: Introductionmentioning
confidence: 99%